2006
DOI: 10.3844/ajassp.2006.1730.1734
|View full text |Cite
|
Sign up to set email alerts
|

cDNA Microarray Genome Image Processing Using Fixed Spot Position

Abstract: Abstract:Complementary DNA (cDNA) microarray is one of the most recent and important technology for exploring the genome. cDNA microarray Image analysis aims to measure the intensity for each spot in the scanned image and this intensity represents the amount of a specific gene in the studied cell. This paper presents a new algorithm that achieves an automated way for applying grid in the cDNA microarray images through the determination of spots position in the cDNA microarray and calculating the mean of every … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Fig. 1: a. RGB color microarray image, b. Grayscale microarray image Gridding is performed in an automated way assuming the positions of spots are fixed [22]. Although the size and intensity of each spot is different from each other, the spots are located on the microarray image in an order.…”
Section: Resultsmentioning
confidence: 99%
“…Fig. 1: a. RGB color microarray image, b. Grayscale microarray image Gridding is performed in an automated way assuming the positions of spots are fixed [22]. Although the size and intensity of each spot is different from each other, the spots are located on the microarray image in an order.…”
Section: Resultsmentioning
confidence: 99%
“…This applicable method can correctly grid all the four types of microarray images without any human intervention. By comparing our method with other methods as those implemented by Deepa J and Tessamma Thomas [20] and Basim Alhadidi [21], it was found that our method is more accurate and can grid various types of noisy images correctly as it mainly deals with noisy images. It should be noted that the processing time for the gridding of the four various types of microarray images, was lower than 6 sec.…”
Section: A Very Good Imagementioning
confidence: 96%
“…The adaptive shape segmentation segments a spots by its shape either by the seeded region growing (SRG) ( Bariamis et al, 2010) or the globally optimal geodesic active contours (GOGAC) (Alhadidi et al, 2006). The spot is adaptive in size and can be of irregular shape.…”
Section: Literature Reviewmentioning
confidence: 99%